2017
DOI: 10.21500/20112084.2608
|View full text |Cite
|
Sign up to set email alerts
|

Socio-cognitive and personal characteristics of young offenders: a field study

Abstract: Adolescence is characterised by a higher prevalence of risk-taking and the challenging of social norms, which appears to bear a relationship to personal abilities and social-cognitive deficits. With the aim of understanding this relationship, a comparative study was undertaken with two groups of adolescents, one belonging to the standard population and one comprising young people who have been subject to correctional measures. In order to evaluate the variables involved, use was made of the Questionnaire for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…The link between well‐being and family contact highlights how vital emotional ties are to the well‐being of incarcerated young people, as also noted by Borrás et al. (2017). This evidence too has direct implications for rehabilitation efforts, which must actively promote and strengthen family connections.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The link between well‐being and family contact highlights how vital emotional ties are to the well‐being of incarcerated young people, as also noted by Borrás et al. (2017). This evidence too has direct implications for rehabilitation efforts, which must actively promote and strengthen family connections.…”
Section: Discussionsupporting
confidence: 60%
“…Armstrong & McGhee, 2019;Shulman et al, 2021;van de Weijer, 2022), family contact stands out as one of the most critical factors in reducing vulnerability. The link between well-being and family contact highlights how vital emotional ties are to the well-being of incarcerated young people, as also noted by Borrás et al (2017). This evidence too has direct implications for rehabilitation efforts, which must actively promote and strengthen family connections.…”
Section: Discussionmentioning
confidence: 70%
“…According to the last results of the Spanish National Statistics Institute (National Statistics Institute, 2019), the number of young people reported for gender violence, compared with the previous year, increased by 14.1% at ages 18 to 19 and by 11.9% at ages 25 to 29. Therefore, studies are focusing on the youngest couples because, in this stage, risky behaviors prevail (Borrás et al, 2017) and, in consequence, violent dynamics increase and start to be considered acceptable (Kidman & Kohler, 2020). Dating violence develops differently than adult intimate partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, men and women deliberately learn to use violent behaviours to harm their partners (Echeburúa 2019;Ibabe et al 2020;Salguero-Alcañiz et al 2023;Zamora-Damián et al 2018). Violence in couple relationships tends to begin progressively, with a higher frequency at early ages (Borrás et al 2017;Rubio-Garay et al 2017). In this sense, it is considered necessary to continue advancing the associated study and analyse how the gender roles observed in one's family and peer group influence their perceptions and attitudes towards intimate partner violence, and it would be interesting to know its relationship with the socioeconomic and educational levels of one's family.…”
Section: Discussionmentioning
confidence: 99%